Action, design & research: A process meta-model - Henriques, T. (2020)
Conducting Action and Design Research within organizations - with the objective of solving multidimensional problems, promoting effective change, developing useful artifacts, and generating actionable knowledge - involves the iterative application of a rigorous set of integrated processes. In a previous publication - based on empirical work, on a comprehensive literature review, and the practice of applying it to teach graduate students on qualitative research methods - a high-level conceptual model for Action & Design Research has been developed and published. It has identified - through the presentation of a tri-dimensional perspective, under the form of a cube - the essential processes and data components, emerging from the Organization Development, Engineering, and Science perspectives. Based on that high-level conceptual view, the objective of the current article is to detail a pragmatic approach to the main activities which are involved in the Action and Design Science Research approaches - under the form of high-level Process Meta-Models.